Development of a scale for measuring user computer experience. - Yaghmaie F (Journal of Research in Nursing, 2007)
The use of computers at work has resulted in researchers searching for factors that affect computer performance and usage. One of the factors that has been identified is user computer experience. However there does not seem to be any consensus on the definition or construct of this. Researchers have either used one-item scales of prior experience or measured the years of experience or number of applications used. Some have recognised the need for multiple measures (Szajna and Mackay, 1995), as it is a multi-dimensional construct. Weil, Rosen, and Wugalter (1990) argued that computer experience measured by such objective measures alone would not necessitate positive attitudes as the subjective nature of experience is important. There is a need for a valid and reliable measure of subjective computer experience for future research on information systems.The purpose of this study was to develop a scale for measuring subjective computer experience and test its reliability and validity. Item construction was undertaken following a thorough search of the literature, focus groups and interviews with computer experts and users. The subjective computer experience scale (SCES) with 38 Likert-type items was tested for content validity by a panel of ten experts and face validity by 15 students. Following these processes, the scale was reduced to 25 items. The 25-item SCES was distributed to 202 second- and third-year computer science and business students along with Dambrot's Computer Attitude Scale (CATT). A test-retest of SCES was given to 162 of the same students. Following Principal Component Analysis, a 12-item scale with two factors was selected. An Internal Consistency reliability of 0.97 and 0.66 and a test-retest reliability of 0.80 or 0.65 were found for the two factors. The two factors correlate with the CATT scale of 0.62 and 0.36 respectively. A useful measure of subjective computer experience has been developed, but it needs further validation in different settings.